Implementation Gap Analysis of National Electronic Health Record (EHR) Data Security Standards in Primary Healthcare Facilities - Destri Maya Rani; Windatania Mayasari; Riska Faraswati; Dafrosa Luni; Nikmatul Firdaus (CV. Get Press Indonesia, 2025)
This study examines the gap between national Electronic Health Record (EHR) data security standards, established by Minister of Health Regulation No. 24 of 2022, and their implementation in Indonesia’s primary healthcare facilities. Secondary data from the Ministry of Health, BSSN, and BPJS Kesehatan (2020–2025) reveal compliance rates of 55%–70%, with significant regional disparities linked to infrastructure and staff training deficiencies. Regression analysis shows staff training intensity (β = 0.54, p = .001) and infrastructure quality (β = 0.47, p = .005) as key predictors, explaining 72% of compliance differences. The findings highlight challenges in technology, human resources, and governance. Urgent integration of technological upgrades and continuous role-based cybersecurity training is recommended to enhance accountability and secure the digital health ecosystem. These insights inform national policy for standardized cybersecurity practices.